2010
DOI: 10.1167/iovs.10-5669
|View full text |Cite
|
Sign up to set email alerts
|

Antifibrotic Activity of Bevacizumab on Human Tenon's Fibroblasts In Vitro

Abstract: Bevacizumab disrupted fibroblast proliferation, inhibited collagen gel contraction ability, and induced fibroblast cell death at concentrations greater than 7.5 mg/mL in serum-free conditions. These results demonstrated that bevacizumab inhibited a number of fibrosis activities in culture. These activities may underpin the antifibrosis effect proposed in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 40 publications
4
44
0
5
Order By: Relevance
“…25,26 Second, there are evidences of direct effect of VEGF on fibroblasts, which if inhibited by anti-VEGF agents, scar formation process could be modulated. [27][28][29][30] The goal of this study was to compare the outcome of primary trabeculectomy in open-angle glaucoma patients with or without adjunctive intracameral bevacizumab. No antifibrotic agents (MMC or 5-FU) were used in our patients.…”
Section: Methodsmentioning
confidence: 99%
“…25,26 Second, there are evidences of direct effect of VEGF on fibroblasts, which if inhibited by anti-VEGF agents, scar formation process could be modulated. [27][28][29][30] The goal of this study was to compare the outcome of primary trabeculectomy in open-angle glaucoma patients with or without adjunctive intracameral bevacizumab. No antifibrotic agents (MMC or 5-FU) were used in our patients.…”
Section: Methodsmentioning
confidence: 99%
“…The ability of anti-VEGF agents (such as bevacizumab at a standard 1.25 mg/0.05 mL concentration) to inhibit the proliferation and migration of Tenon fibroblasts has been well documented 7 8. The use of anti-VEGF agents may be particularly interesting in glaucoma patients, since they have increased concentrations of VEGF in the aqueous humour 7 9…”
Section: Introductionmentioning
confidence: 99%
“…Vascular endothelial growth factor also affects a fibroblastic activity in addition to angiogenesis [40]. In a study by Evelyn et al, found that bevacizumab disrupted fibroblast proliferation, and the constriction ability of collagen gel was disabled [41].…”
Section: Discussionmentioning
confidence: 99%